Waterproof anti-crack latex paint and preparation method thereof
Through the combination of the modification emulsion and a variety of additives, a waterproof and crack-resistant latex paint with excellent performance was prepared, which solved the shortcomings of existing latex paints in waterproof and crack-resistant properties, and achieved better waterproof, crack-resistant and anti-aging effects.
Patent Information
- Application Number
- CN202411749583.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing latex paint has shortcomings in waterproof and crack resistance, and cannot effectively solve the problems of water leakage and seepage on the walls of buildings.
A waterproof and crack-resistant latex paint with excellent performance is prepared by combining modified emulsion, modified kaolin, modified cellulose, perfluorohexylethylene, azobisisobutyronitrile, deionized water, multifunctional additive AMP-95, dispersant CF-10, dodecanol ester, propylene glycol and defoaming agent A10.
This latex paint has excellent performance in waterproof, crack resistance, antibacterial and anti-aging properties. It can effectively prevent wall leakage and seepage and improve the living quality of buildings.
Smart Images

Figure BDA0005164663250000031 
Figure BDA0005164663250000032 
Figure BDA0005164663250000041
Abstract
Description
Technical Field
[0001] The invention relates to the field of latex paint, in particular to a waterproof and crack-resistant latex paint and a preparation method thereof. Background Art
[0002] Latex paint is a type of water-based paint that uses water as a dispersion medium and polymer emulsion as a film-forming substance. It is synthesized by adding pigments, fillers and additives through a certain process. Due to its good decorative effect, convenient construction and low environmental pollution, latex paint has become the main product of interior decoration materials. Latex paint has a series of advantages such as low cost and the ability to mix different color paints according to different color schemes, and is widely used in the construction industry.
[0003] Latex paint mainly includes two categories: interior wall latex paint and exterior wall latex paint. It not only decorates the wall surface but also has a protective function for the building. Therefore, as a wall building paint, it should also have other special functions. Waterproofing is the most important and most needed function of wall paint at present. Due to various reasons, many building walls have different degrees of leakage and seepage, which seriously affects the quality of living. Therefore, the present invention prepares a waterproof and crack-resistant latex paint with excellent performance. Summary of the invention
[0004] The purpose of the present invention is to provide a waterproof and crack-resistant latex paint and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] The invention discloses a waterproof and crack-resistant latex paint, which is obtained by uniformly mixing modified emulsion, modified kaolin, modified cellulose, perfluorohexylethylene, azobisisobutyronitrile, deionized water, multifunctional auxiliary agent AMP-95, dispersant CF-10, dodecyl alcohol ester, propylene glycol and defoamer A10.
[0007] As an optimization, the modified cellulose is obtained by reacting cellulose powder and methacrylic anhydride.
[0008] As an optimization, the cellulose powder model is 120 mesh and comes from Kaimaoxing (Hebei) Cellulose Co., Ltd.
[0009] As an optimization, the modified emulsion is obtained by reacting dicyandiamide with 2-amino-4,6-dichloro-S-triazine, resorcinol, and 4-vinylbenzaldehyde in sequence, and then reacting with acrylate, butyl acrylate, and 1,3-butadiene.
[0010] As an optimization, the modified kaolin is obtained by reacting calcined kaolin with 3-chloropropyltrimethoxysilane and allyldiphenylphosphine in sequence.
[0011] As an optimization, the calcined kaolin 325 mesh comes from Baiyi Mineral Products Processing Plant in Lingshou County.
[0012] A method for preparing a waterproof and crack-resistant latex paint comprises the following preparation steps:
[0013] (1) Calcined kaolin, 3-chloropropyltrimethoxysilane and ethanol solution with a mass fraction of 85% to 95% are mixed in a mass ratio of 1: (0.9 to 1.1): (40 to 50), stirred at 65 to 75°C and 200 to 300 rpm for 4 to 6 hours, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol for 3 to 5 times respectively, and dried at 55 to 65°C for 11 to 13 hours to obtain a pre-modified kaolin. Kaolin; pre-modified kaolin, allyl diphenylphosphine, nickel bromide and ethylene glycol are mixed in a mass ratio of 1: (1.1-1.3): (0.01-0.02): (8-10), stirred in a nitrogen atmosphere at 155-165° C. and 100-200 rpm for 4-6 hours, naturally cooled to room temperature and then filtered, washed with deionized water for 3-5 times, and dried at 50-60° C. for 14-16 hours to obtain modified kaolin;
[0014] (2) dicyandiamide, 2-amino-4,6-dichloro-S-triazine and isopropanol are mixed in a mass ratio of 1:(1.9-2.1):(14-16), and a 35%-37% hydrochloric acid solution having a mass fraction of 1.03-1.05 times the mass of dicyandiamide is added at a constant rate at 95-105° C. for 1-3 h, refluxed for 6-8 h, rotary evaporated at 80-90° C. for 1-2 h, dissolved in anhydrous methanol and filtered, rotary evaporated at 40-50° C. for 1-2 h, recrystallized with a mass fraction of 4%-6% ethanol solution and filtered, and dried at 50-60° C. for 8-10 h to obtain a biguanide intermediate; the biguanide intermediate, resorcinol, anhydrous aluminum chloride and chlorobenzene are mixed in a mass ratio of 1:(0.4-0.6):(0.2-0.4):( 9-11) mix, stir at 75-85° C. and 100-200 rpm for 3-5 h, add 1%-3% hydrochloric acid solution with a mass fraction of 9-10 times the mass of the biguanide intermediate at a uniform rate within 1-3 h, distill at atmospheric pressure, heat to 95-105° C., filter while hot, wash with 1%-3% hydrochloric acid solution and deionized water for 3-5 times, dry at 55-65° C. for 11-13 h to obtain functionalized biguanide; mix 4-vinylbenzaldehyde, functionalized biguanide and anhydrous ethanol at a mass ratio of 1:(0.3-0.5):(20-30), stir at 45-55° C. and 200-300 rpm in a nitrogen atmosphere for 5-7 h, and rotary evaporate at 50-60° C. for 20-30 min to obtain a modified monomer;
[0015] (3) Mix potassium persulfate and deionized water at a mass ratio of 1:100 to obtain an initiator solution; mix acrylate, butyl acrylate, modified monomer, 1,3-butadiene and emulsifier mixed solution at a mass ratio of 1:(9-11):(8.4-8.6):(4-6):(53-54), pre-emulsify at 35-45°C and 275-285r / min for 55-65min, heat to 75-85°C, add an initiator solution of 11.5-11.7 times the mass of acrylic acid at a uniform rate within 25-35min, continue stirring for 1-2h, heat to 85-95°C, add an initiator solution of 5.7-5.9 times the mass of acrylic acid at a uniform rate within 25-35min, continue stirring for 1-2h, cool naturally to room temperature, and filter with a 100-200 mesh sieve to obtain a modified emulsion;
[0016] (4) Mixing cellulose powder and sodium hydroxide solution with a mass fraction of 10% to 20% at a mass ratio of 1:(15-25), soaking for 25-35 minutes, filtering, washing with deionized water for 3-5 times, and then soaking in N,N-dimethylacetamide for 11-13 hours, filtering to obtain activated cellulose; mixing activated cellulose, methacrylic anhydride, lithium chloride-free and N,N-dimethylacetamide at a mass ratio of 1:(1.5-2.5):(0.9-1.1):(9-11), stirring at 55-65° C. and 200-300 rpm for 5-7 hours, adding deionized water and standing until the precipitate mass remains unchanged, filtering, washing with deionized water for 3-5 times, and freeze-drying to obtain modified cellulose;
[0017] (5) According to the mass fraction, 89-91 parts of modified latex, 4-6 parts of modified kaolin, 1-3 parts of modified cellulose, 0.3-0.5 parts of perfluorohexylethylene, 0.01-0.03 parts of azobisisobutyronitrile and 5-15 parts of deionized water are dispersed at 1200-1400 rpm for 55-65 min, 0.01-0.02 parts of multifunctional auxiliary agent AMP-95, 0.08-0.10 parts of dispersant CF-10, 0.07-0.08 parts of dodecyl alcohol ester, 0.07-0.08 parts of propylene glycol and 0.03-0.05 parts of defoamer A10 are added, and the mixture is stirred at 900-1100 r / min for 25-35 min to obtain a waterproof and crack-resistant latex paint.
[0018] As an optimization, the reaction equation of the pre-modified kaolin in step (1) is:
[0019]
[0020] As an optimization, the reaction equation of the modified kaolin in step (1) is:
[0021]
[0022] As an optimization, the reaction equation of the biguanide intermediate in step (2) is:
[0023]
[0024] As an optimization, the reaction equation of the functionalized biguanide in step (2) is:
[0025]
[0026] As an optimization, the reaction equation of the modified monomer in step (2) is:
[0027]
[0028] As an optimization, the emulsifier mixed solution in step (3) is obtained by mixing sodium dodecylbenzene sulfonate, Tween-80 and deionized water in a mass ratio of 1:2.12:100.
[0029] As an optimization, the reaction equation of the modified latex in step (3) is:
[0030]
[0031] As an optimization, the reaction equation for the modified cellulose in step (4) is:
[0032]
[0033] Where R is H or
[0034] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0035] When preparing the waterproof and crack-resistant latex paint, the present invention comprises the following steps: reacting calcined kaolin with 3-chloropropyltrimethoxysilane and allyldiphenylphosphine in sequence to obtain modified kaolin; reacting dicyandiamide with 2-amino-4,6-dichloro-S-triazine, resorcinol and 4-vinylbenzaldehyde in sequence to obtain a modified monomer; reacting acrylate, butyl acrylate, the modified monomer and 1,3-butadiene to obtain a modified emulsion; reacting cellulose powder with methacrylic anhydride to obtain modified cellulose; and uniformly mixing the modified emulsion, modified kaolin, modified cellulose, perfluorohexylethylene, azobisisobutyronitrile, deionized water, multifunctional auxiliary agent AMP-95, dispersant CF-10, dodecanol ester, propylene glycol and defoamer A10 to obtain the waterproof and crack-resistant latex paint.
[0036] First, calcined kaolin is reacted with 3-chloropropyltrimethoxysilane and allyl diphenylphosphine in sequence to obtain modified kaolin; dicyandiamide is reacted with 2-amino-4,6-dichloro-S-triazine, resorcinol and 4-vinylbenzaldehyde in sequence to obtain a modified monomer; acrylate, butyl acrylate, modified monomer and 1,3-butadiene are then reacted to obtain a modified latex; a quaternary phosphonium salt structure similar to the structure and antibacterial mechanism of quaternary ammonium salt antibacterial agent is formed on calcined kaolin, phosphorus has a larger atomic radius than nitrogen, has a lower corresponding electronegativity, is more positively charged, and has a stronger attraction to negatively charged bacterial cell membranes, thereby improving the antibacterial property of waterproof and crack-resistant latex paint; a biguanide structure is introduced by reacting dicyandiamide with 2-amino-4,6-dichloro-S-triazine, and the guanidine group can be ionized It carries positive charge and contacts microbial cells through electrostatic attraction, further improving the antibacterial property of waterproof and anti-cracking latex paint; it undergoes substitution reaction with resorcinol to construct intramolecular hydrogen bonds, giving the modified monomer the ability to absorb ultraviolet rays, further improving the anti-aging property of waterproof and anti-cracking latex paint; 4-vinylbenzaldehyde is grafted through Schiff base reaction, carbon-carbon double bonds are introduced into the modified monomer, participating in the polymerization of acrylic emulsion to form stable chemical bonds, thus improving the stability of waterproof and anti-cracking latex paint; conjugated diene 1,3-butadiene forms new covalent bonds after the double bonds are opened by addition polymerization, retaining the carbon-carbon double bonds in the main chain of the modified emulsion, and can be cross-linked with modified kaolin and modified cellulose in the subsequent curing process to enrich the cross-linking network and improve the crack resistance of waterproof and anti-cracking latex paint.
[0037] Secondly, cellulose powder and methacrylic anhydride are reacted to obtain modified cellulose; modified latex, modified kaolin, modified cellulose, perfluorohexylethylene, azobisisobutyronitrile, deionized water, multifunctional additive AMP-95, dispersant CF-10, dodecyl alcohol ester, propylene glycol, and defoamer A10 are mixed to obtain waterproof and crack-resistant latex paint; a large number of hydroxyl groups on cellulose are reacted with acid anhydride to graft carbon-carbon double bonds, which are cross-linked with the carbon-carbon double bonds on the modified kaolin and the modified latex to form a network, thereby improving the crack resistance of the waterproof and crack-resistant latex paint; perfluorohexylethylene is used to participate in curing and cross-linking, and hydrophobic perfluorinated long chains are introduced to improve the waterproof performance of the waterproof and crack-resistant latex paint. DETAILED DESCRIPTION
[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0039] Embodiment 1:
[0040] A method for preparing a waterproof and crack-resistant latex paint, comprising the following preparation steps:
[0041] (1) Calcined kaolin, 3-chloropropyltrimethoxysilane and 85% ethanol solution were mixed in a mass ratio of 1:0.9:40, stirred at 65°C and 200 rpm for 6 h, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol for 3 times, respectively, and dried at 55°C for 13 h to obtain pre-modified kaolin; pre-modified kaolin, allyl diphenylphosphine, nickel bromide and ethylene glycol were mixed in a mass ratio of 1:1.1:0.01:8, stirred at 155°C and 100 rpm for 6 h in a nitrogen atmosphere, naturally cooled to room temperature and filtered, washed with deionized water for 3 times, and dried at 50°C for 16 h to obtain modified kaolin;
[0042] (2) dicyandiamide, 2-amino-4,6-dichloro-S-triazine and isopropanol were mixed at a mass ratio of 1:1.9:14, and a 35% hydrochloric acid solution with a mass fraction of 1.03 times the mass of dicyandiamide was added at a constant rate for 1 hour at 95°C, refluxed for 8 hours, rotary evaporated at 80°C for 2 hours, dissolved in anhydrous methanol and filtered, rotary evaporated at 40°C for 2 hours, recrystallized with a mass fraction of 4% ethanol solution and filtered, and dried at 50°C for 10 hours to obtain a biguanide intermediate; the biguanide intermediate, resorcinol, anhydrous aluminum chloride and chlorobenzene were mixed at a mass ratio of 1:0.4:0.2 :9, stir at 75°C and 100rpm for 5h, add 1% hydrochloric acid solution with a mass fraction of 9 times the mass of the biguanide intermediate at a uniform rate within 1h, distill at atmospheric pressure, heat to 95°C, filter while hot, wash with 1% hydrochloric acid solution and deionized water for 3 times respectively, dry at 55°C for 13h to obtain functionalized biguanide; mix 4-vinylbenzaldehyde, functionalized biguanide and anhydrous ethanol at a mass ratio of 1:0.3:20, stir at 45°C and 200rpm in a nitrogen atmosphere for 7h, and rotary evaporate at 50°C for 30min to obtain a modified monomer;
[0043] (3) Potassium persulfate and deionized water are mixed at a mass ratio of 1:100 to obtain an initiator solution; acrylate, butyl acrylate, modified monomer, 1,3-butadiene and emulsifier mixed solution are mixed at a mass ratio of 1:9:8.4:4:53, pre-emulsified at 35°C and 275r / min for 65min, heated to 75°C, and added with an initiator solution of 11.5 times the mass of acrylic acid at a uniform rate within 25min, continued to stir for 2h, heated to 85°C, and added with an initiator solution of 5.7 times the mass of acrylic acid at a uniform rate within 25min, continued to stir for 2h, cooled naturally to room temperature, and filtered with a 100-mesh sieve to obtain a modified emulsion;
[0044] (4) Mix cellulose powder and 10% sodium hydroxide solution in a mass ratio of 1:15, soak for 25 minutes, filter, wash with deionized water for 3 times, soak in N,N-dimethylacetamide for 11 hours, and filter to obtain activated cellulose; Mix activated cellulose, methacrylic anhydride, lithium chloride-free and N,N-dimethylacetamide in a mass ratio of 1:1.5:0.9:9, stir at 55°C and 200 rpm for 7 hours, add deionized water and let stand until the precipitate mass remains unchanged, filter, wash with deionized water for 3 times, and freeze-dry to obtain modified cellulose;
[0045] (5) According to the mass fraction, 89 parts of modified latex, 4 parts of modified kaolin, 1 part of modified cellulose, 0.3 parts of perfluorohexylethylene, 0.01 parts of azobisisobutyronitrile and 5 parts of deionized water were dispersed at 1200 rpm for 65 min, 0.01 parts of multifunctional auxiliary agent AMP-95, 0.08 parts of dispersant CF-10, 0.07 parts of dodecyl alcohol ester, 0.07 parts of propylene glycol and 0.03 parts of defoamer A10 were added, and stirred at 900 r / min for 35 min to obtain a waterproof and crack-resistant latex paint.
[0046] Embodiment 2:
[0047] A method for preparing a waterproof and crack-resistant latex paint, comprising the following preparation steps:
[0048] (1) Calcined kaolin, 3-chloropropyltrimethoxysilane and 90% ethanol solution were mixed in a mass ratio of 1:1:45, stirred at 70°C and 250 rpm for 5 h, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol for 4 times, respectively, and dried at 60°C for 12 h to obtain pre-modified kaolin; pre-modified kaolin, allyl diphenylphosphine, nickel bromide and ethylene glycol were mixed in a mass ratio of 1:1.2:0.015:9, stirred at 160°C and 150 rpm for 5 h in a nitrogen atmosphere, naturally cooled to room temperature and filtered, washed with deionized water for 4 times, and dried at 55°C for 15 h to obtain modified kaolin;
[0049] (2) Dicyandiamide, 2-amino-4,6-dichloro-S-triazine and isopropanol were mixed at a mass ratio of 1:2:15, and a 36% hydrochloric acid solution with a mass fraction of 1.04 times the mass of dicyandiamide was added at a constant rate for 2 hours at 100° C., refluxed for 7 hours, rotary evaporated at 85° C. for 1.5 hours, dissolved in anhydrous methanol and filtered, rotary evaporated at 45° C. for 1.5 hours, recrystallized with a 5% ethanol solution and filtered, and dried at 55° C. for 9 hours to obtain a biguanide intermediate; the biguanide intermediate, resorcinol, anhydrous aluminum chloride and chlorobenzene were mixed at a mass ratio of 1:0.5:0.3: 10, stir at 80 ° C and 150 rpm for 4 hours, add 2% hydrochloric acid solution with a mass fraction of 9.5 times the mass of the biguanide intermediate at a uniform rate within 2 hours, distill at atmospheric pressure, heat to 100 ° C, filter while hot, wash with 2% hydrochloric acid solution and deionized water for 4 times, dry at 60 ° C for 12 hours to obtain functionalized biguanide; 4-vinylbenzaldehyde, functionalized biguanide and anhydrous ethanol are mixed at a mass ratio of 1:0.4:25, stir at 50 ° C and 250 rpm for 6 hours in a nitrogen atmosphere, and rotary evaporate at 55 ° C for 25 minutes to obtain a modified monomer;
[0050] (3) Potassium persulfate and deionized water are mixed at a mass ratio of 1:100 to obtain an initiator solution; acrylate, butyl acrylate, modified monomer, 1,3-butadiene and emulsifier mixed solution are mixed at a mass ratio of 1:10:8.5:5:53.5, pre-emulsified at 40°C and 280r / min for 60min, heated to 80°C, and added with an initiator solution of 11.6 times the mass of acrylic acid at a uniform rate within 30min, continued to stir for 1.5h, heated to 90°C, and added with an initiator solution of 5.8 times the mass of acrylic acid at a uniform rate within 30min, continued to stir for 1.5h, cooled naturally to room temperature, and filtered with a 150-mesh sieve to obtain a modified emulsion;
[0051] (4) Mix cellulose powder and 15% sodium hydroxide solution in a mass ratio of 1:20, soak for 30 minutes, filter, wash with deionized water 4 times, soak in N,N-dimethylacetamide for 12 hours, and filter to obtain activated cellulose; Mix activated cellulose, methacrylic anhydride, lithium chloride-free and N,N-dimethylacetamide in a mass ratio of 1:2:1:10, stir at 60°C and 250rpm for 6 hours, add deionized water and let stand until the precipitate mass remains unchanged, filter, wash with deionized water 4 times, and freeze-dry to obtain modified cellulose;
[0052] (5) According to the mass fraction, 90 parts of modified latex, 5 parts of modified kaolin, 2 parts of modified cellulose, 0.4 parts of perfluorohexylethylene, 0.02 parts of azobisisobutyronitrile and 10 parts of deionized water were dispersed at 1300 rpm for 60 min, 0.015 parts of multifunctional additive AMP-95, 0.09 parts of dispersant CF-10, 0.075 parts of dodecyl alcohol ester, 0.075 parts of propylene glycol and 0.04 parts of defoamer A10 were added, and stirred at 1000 r / min for 30 min to obtain a waterproof and crack-resistant latex paint.
[0053] Embodiment 3:
[0054] A method for preparing a waterproof and crack-resistant latex paint, comprising the following preparation steps:
[0055] (1) Calcined kaolin, 3-chloropropyltrimethoxysilane and 95% ethanol solution were mixed in a mass ratio of 1:1.1:50, stirred at 75°C and 300 rpm for 4 h, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol for 5 times, respectively, and dried at 65°C for 11 h to obtain pre-modified kaolin; pre-modified kaolin, allyl diphenylphosphine, nickel bromide and ethylene glycol were mixed in a mass ratio of 1:1.3:0.02:10, stirred at 165°C and 200 rpm for 4 h in a nitrogen atmosphere, naturally cooled to room temperature and filtered, washed with deionized water for 5 times, and dried at 60°C for 14 h to obtain modified kaolin;
[0056] (2) Dicyandiamide, 2-amino-4,6-dichloro-S-triazine and isopropanol were mixed at a mass ratio of 1:2.1:16, and a 37% hydrochloric acid solution with a mass fraction of 1.05 times the mass of dicyandiamide was added at a constant rate for 3 hours at 105° C., refluxed for 6 hours, rotary evaporated at 90° C. for 1 hour, dissolved in anhydrous methanol and filtered, rotary evaporated at 50° C. for 1 hour, recrystallized with a mass fraction of 6% ethanol solution and filtered, and dried at 60° C. for 8 hours to obtain a biguanide intermediate; the biguanide intermediate, resorcinol, anhydrous aluminum chloride and chlorobenzene were mixed at a mass ratio of 1:0.6:0.4: 11, stir at 85 ° C and 200 rpm for 3 hours, add 3% hydrochloric acid solution with a mass fraction of 10 times the mass of the biguanide intermediate at a uniform rate within 3 hours, distill at atmospheric pressure, heat to 105 ° C, filter while hot, wash with 3% hydrochloric acid solution and deionized water for 5 times, dry at 65 ° C for 11 hours to obtain functionalized biguanide; 4-vinylbenzaldehyde, functionalized biguanide and anhydrous ethanol are mixed at a mass ratio of 1:0.5:30, stir at 55 ° C and 300 rpm for 5 hours in a nitrogen atmosphere, and rotary evaporate at 60 ° C for 20 minutes to obtain a modified monomer;
[0057] (3) Potassium persulfate and deionized water are mixed at a mass ratio of 1:100 to obtain an initiator solution; acrylate, butyl acrylate, modified monomer, 1,3-butadiene and emulsifier mixed solution are mixed at a mass ratio of 1:11:8.6:6:54, pre-emulsified at 45°C and 285r / min for 55min, heated to 85°C, and added with an initiator solution of 11.7 times the mass of acrylic acid at a uniform rate within 35min, continued to stir for 1h, heated to 95°C, and added with an initiator solution of 5.9 times the mass of acrylic acid at a uniform rate within 35min, continued to stir for 1h, cooled naturally to room temperature, and filtered with a 200-mesh sieve to obtain a modified emulsion;
[0058] (4) Mix cellulose powder and 20% sodium hydroxide solution in a mass ratio of 1:25, soak for 35 minutes, filter, wash with deionized water for 5 times, soak in N,N-dimethylacetamide for 13 hours, and filter to obtain activated cellulose; Mix activated cellulose, methacrylic anhydride, lithium chloride-free and N,N-dimethylacetamide in a mass ratio of 1:2.5:1.1:11, stir at 65°C and 300 rpm for 5 hours, add deionized water and let stand until the precipitate mass remains unchanged, filter, wash with deionized water for 5 times, and freeze-dry to obtain modified cellulose;
[0059] (5) According to the mass fraction, 91 parts of modified latex, 6 parts of modified kaolin, 3 parts of modified cellulose, 0.5 parts of perfluorohexylethylene, 0.03 parts of azobisisobutyronitrile and 15 parts of deionized water were dispersed at 1400 rpm for 55 min, 0.02 parts of multifunctional additive AMP-95, 0.10 parts of dispersant CF-10, 0.08 parts of dodecyl alcohol ester, 0.08 parts of propylene glycol and 0.05 parts of defoamer A10 were added, and stirred at 1100 r / min for 25 min to obtain a waterproof and crack-resistant latex paint.
[0060] Comparative Example 1:
[0061] A method for preparing a waterproof and crack-resistant latex paint, comprising the following preparation steps:
[0062] (1) Dicyandiamide, 2-amino-4,6-dichloro-S-triazine and isopropanol are mixed at a mass ratio of 1:2:15, and a 36% hydrochloric acid solution having a mass fraction of 1.04 times the mass of dicyandiamide is added at a constant rate for 2 hours at 100° C., refluxed for 7 hours, rotary evaporated at 85° C. for 1.5 hours, dissolved in anhydrous methanol and filtered, rotary evaporated at 45° C. for 1.5 hours, recrystallized with a 5% ethanol solution and filtered, and dried at 55° C. for 9 hours to obtain a biguanide intermediate; the biguanide intermediate, resorcinol, anhydrous aluminum chloride and chlorobenzene are mixed at a mass ratio of 1:0.5:0.3: 10, stir at 80 ° C and 150 rpm for 4 hours, add 2% hydrochloric acid solution with a mass fraction of 9.5 times the mass of the biguanide intermediate at a uniform rate within 2 hours, distill at atmospheric pressure, heat to 100 ° C, filter while hot, wash with 2% hydrochloric acid solution and deionized water for 4 times, dry at 60 ° C for 12 hours to obtain functionalized biguanide; 4-vinylbenzaldehyde, functionalized biguanide and anhydrous ethanol are mixed at a mass ratio of 1:0.4:25, stir at 50 ° C and 250 rpm for 6 hours in a nitrogen atmosphere, and rotary evaporate at 55 ° C for 25 minutes to obtain a modified monomer;
[0063] (2) Potassium persulfate and deionized water are mixed at a mass ratio of 1:100 to obtain an initiator solution; acrylate, butyl acrylate, modified monomer, 1,3-butadiene and emulsifier mixed solution are mixed at a mass ratio of 1:10:8.5:5:53.5, pre-emulsified at 40°C and 280r / min for 60min, heated to 80°C, and added with an initiator solution of 11.6 times the mass of acrylic acid at a uniform rate within 30min, continued to stir for 1.5h, heated to 90°C, and added with an initiator solution of 5.8 times the mass of acrylic acid at a uniform rate within 30min, continued to stir for 1.5h, cooled naturally to room temperature, and filtered with a 150-mesh sieve to obtain a modified emulsion;
[0064] (3) Mix cellulose powder and 15% sodium hydroxide solution in a mass ratio of 1:20, soak for 30 minutes, filter, wash with deionized water 4 times, soak in N,N-dimethylacetamide for 12 hours, and filter to obtain activated cellulose; Mix activated cellulose, methacrylic anhydride, lithium chloride-free and N,N-dimethylacetamide in a mass ratio of 1:2:1:10, stir at 60°C and 250 rpm for 6 hours, add deionized water and let stand until the precipitate mass remains unchanged, filter, wash with deionized water 4 times, and freeze-dry to obtain modified cellulose;
[0065] (4) According to the mass fraction, 90 parts of modified latex, 5 parts of calcined kaolin, 2 parts of modified cellulose, 0.4 parts of perfluorohexylethylene, 0.02 parts of azobisisobutyronitrile and 10 parts of deionized water were dispersed at 1300 rpm for 60 min, 0.015 parts of multifunctional auxiliary agent AMP-95, 0.09 parts of dispersant CF-10, 0.075 parts of dodecyl alcohol ester, 0.075 parts of propylene glycol and 0.04 parts of defoamer A10 were added, and stirred at 1000 r / min for 30 min to obtain a waterproof and crack-resistant latex paint.
[0066] Comparative Example 2:
[0067] A method for preparing a waterproof and crack-resistant latex paint, comprising the following preparation steps:
[0068] (1) Calcined kaolin, 3-chloropropyltrimethoxysilane and 90% ethanol solution were mixed in a mass ratio of 1:1:45, stirred at 70°C and 250 rpm for 5 h, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol for 4 times, respectively, and dried at 60°C for 12 h to obtain pre-modified kaolin; pre-modified kaolin, allyl diphenylphosphine, nickel bromide and ethylene glycol were mixed in a mass ratio of 1:1.2:0.015:9, stirred at 160°C and 150 rpm for 5 h in a nitrogen atmosphere, naturally cooled to room temperature and filtered, washed with deionized water for 4 times, and dried at 55°C for 15 h to obtain modified kaolin;
[0069] (2) dicyandiamide, 2-amino-4,6-dichloro-S-triazine and isopropanol were mixed in a mass ratio of 1:2:15, and a 36% hydrochloric acid solution with a mass fraction of 1.04 times the mass of dicyandiamide was added at a constant speed at 100° C. for 2 hours, refluxed for 7 hours, rotary evaporated at 85° C. for 1.5 hours, dissolved in anhydrous methanol and filtered, rotary evaporated at 45° C. for 1.5 hours, recrystallized with a 5% ethanol solution and filtered, and dried at 55° C. for 9 hours to obtain a biguanide intermediate; 4-vinylbenzaldehyde, a biguanide intermediate and anhydrous ethanol were mixed in a mass ratio of 1:0.4:25, stirred at 50° C. and 250 rpm for 6 hours in a nitrogen atmosphere, and rotary evaporated at 55° C. for 25 minutes to obtain a modified monomer;
[0070] (3) Potassium persulfate and deionized water are mixed at a mass ratio of 1:100 to obtain an initiator solution; acrylate, butyl acrylate, modified monomer, 1,3-butadiene and emulsifier mixed solution are mixed at a mass ratio of 1:10:8.5:5:53.5, pre-emulsified at 40°C and 280r / min for 60min, heated to 80°C, and added with an initiator solution of 11.6 times the mass of acrylic acid at a uniform rate within 30min, continued to stir for 1.5h, heated to 90°C, and added with an initiator solution of 5.8 times the mass of acrylic acid at a uniform rate within 30min, continued to stir for 1.5h, cooled naturally to room temperature, and filtered with a 150-mesh sieve to obtain a modified emulsion;
[0071] (4) Mix cellulose powder and 15% sodium hydroxide solution in a mass ratio of 1:20, soak for 30 minutes, filter, wash with deionized water 4 times, soak in N,N-dimethylacetamide for 12 hours, and filter to obtain activated cellulose; Mix activated cellulose, methacrylic anhydride, lithium chloride-free and N,N-dimethylacetamide in a mass ratio of 1:2:1:10, stir at 60°C and 250rpm for 6 hours, add deionized water and let stand until the precipitate mass remains unchanged, filter, wash with deionized water 4 times, and freeze-dry to obtain modified cellulose;
[0072] (5) According to the mass fraction, 90 parts of modified latex, 5 parts of modified kaolin, 2 parts of modified cellulose, 0.4 parts of perfluorohexylethylene, 0.02 parts of azobisisobutyronitrile and 10 parts of deionized water were dispersed at 1300 rpm for 60 min, 0.015 parts of multifunctional additive AMP-95, 0.09 parts of dispersant CF-10, 0.075 parts of dodecyl alcohol ester, 0.075 parts of propylene glycol and 0.04 parts of defoamer A10 were added, and stirred at 1000 r / min for 30 min to obtain a waterproof and crack-resistant latex paint.
[0073] Comparative Example 3:
[0074] A method for preparing a waterproof and crack-resistant latex paint, comprising the following preparation steps:
[0075] (1) Calcined kaolin, 3-chloropropyltrimethoxysilane and 90% ethanol solution were mixed in a mass ratio of 1:1:45, stirred at 70°C and 250 rpm for 5 h, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol for 4 times, respectively, and dried at 60°C for 12 h to obtain pre-modified kaolin; pre-modified kaolin, allyl diphenylphosphine, nickel bromide and ethylene glycol were mixed in a mass ratio of 1:1.2:0.015:9, stirred at 160°C and 150 rpm for 5 h in a nitrogen atmosphere, naturally cooled to room temperature and filtered, washed with deionized water for 4 times, and dried at 55°C for 15 h to obtain modified kaolin;
[0076] (2) 2-amino-4,6-dichloro-S-triazine, resorcinol, anhydrous aluminum chloride and chlorobenzene were mixed in a mass ratio of 1:0.5:0.3:10, stirred at 80°C and 150 rpm for 4 hours, and a 2% hydrochloric acid solution with a mass fraction of 9.5 times the mass of 2-amino-4,6-dichloro-S-triazine was added at a uniform rate within 2 hours, distilled at atmospheric pressure, heated to 100°C, filtered while hot, washed with a 2% hydrochloric acid solution and deionized water for 4 times, and dried at 60°C for 12 hours to obtain a functionalized monomer; 4-vinylbenzaldehyde, functionalized monomer and anhydrous ethanol were mixed in a mass ratio of 1:0.4:25, stirred at 50°C and 250 rpm in a nitrogen atmosphere for 6 hours, and rotary evaporated at 55°C for 25 minutes to obtain a modified monomer;
[0077] (3) Potassium persulfate and deionized water are mixed at a mass ratio of 1:100 to obtain an initiator solution; acrylate, butyl acrylate, modified monomer, 1,3-butadiene and emulsifier mixed solution are mixed at a mass ratio of 1:10:8.5:5:53.5, pre-emulsified at 40°C and 280r / min for 60min, heated to 80°C, and added with an initiator solution of 11.6 times the mass of acrylic acid at a uniform rate within 30min, continued to stir for 1.5h, heated to 90°C, and added with an initiator solution of 5.8 times the mass of acrylic acid at a uniform rate within 30min, continued to stir for 1.5h, cooled naturally to room temperature, and filtered with a 150-mesh sieve to obtain a modified emulsion;
[0078] (4) Mix cellulose powder and 15% sodium hydroxide solution in a mass ratio of 1:20, soak for 30 minutes, filter, wash with deionized water 4 times, soak in N,N-dimethylacetamide for 12 hours, and filter to obtain activated cellulose; Mix activated cellulose, methacrylic anhydride, lithium chloride-free and N,N-dimethylacetamide in a mass ratio of 1:2:1:10, stir at 60°C and 250rpm for 6 hours, add deionized water and let stand until the precipitate mass remains unchanged, filter, wash with deionized water 4 times, and freeze-dry to obtain modified cellulose;
[0079] (5) According to the mass fraction, 90 parts of modified latex, 5 parts of modified kaolin, 2 parts of modified cellulose, 0.4 parts of perfluorohexylethylene, 0.02 parts of azobisisobutyronitrile and 10 parts of deionized water were dispersed at 1300 rpm for 60 min, 0.015 parts of multifunctional additive AMP-95, 0.09 parts of dispersant CF-10, 0.075 parts of dodecyl alcohol ester, 0.075 parts of propylene glycol and 0.04 parts of defoamer A10 were added, and stirred at 1000 r / min for 30 min to obtain a waterproof and crack-resistant latex paint.
[0080] Comparative Example 4:
[0081] A method for preparing a waterproof and crack-resistant latex paint, comprising the following preparation steps:
[0082] (1) Calcined kaolin, 3-chloropropyltrimethoxysilane and 90% ethanol solution were mixed in a mass ratio of 1:1:45, stirred at 70°C and 250 rpm for 5 h, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol for 4 times, respectively, and dried at 60°C for 12 h to obtain pre-modified kaolin; pre-modified kaolin, allyl diphenylphosphine, nickel bromide and ethylene glycol were mixed in a mass ratio of 1:1.2:0.015:9, stirred at 160°C and 150 rpm for 5 h in a nitrogen atmosphere, naturally cooled to room temperature and filtered, washed with deionized water for 4 times, and dried at 55°C for 15 h to obtain modified kaolin;
[0083] (2) Dicyandiamide, 2-amino-4,6-dichloro-S-triazine and isopropanol were mixed at a mass ratio of 1:2:15, and a 36% hydrochloric acid solution with a mass fraction of 1.04 times the mass of dicyandiamide was added at a constant rate for 2 hours at 100° C., refluxed for 7 hours, rotary evaporated at 85° C. for 1.5 hours, dissolved in anhydrous methanol and filtered, rotary evaporated at 45° C. for 1.5 hours, recrystallized with a 5% ethanol solution and filtered, and dried at 55° C. for 9 hours to obtain a biguanide intermediate; the biguanide intermediate, resorcinol, anhydrous aluminum chloride and chlorobenzene were mixed at a mass ratio of 1:0.5:0.3: 10, stir at 80 ° C and 150 rpm for 4 hours, add 2% hydrochloric acid solution with a mass fraction of 9.5 times the mass of the biguanide intermediate at a uniform rate within 2 hours, distill at atmospheric pressure, heat to 100 ° C, filter while hot, wash with 2% hydrochloric acid solution and deionized water for 4 times, dry at 60 ° C for 12 hours to obtain functionalized biguanide; 4-vinylbenzaldehyde, functionalized biguanide and anhydrous ethanol are mixed at a mass ratio of 1:0.4:25, stir at 50 ° C and 250 rpm for 6 hours in a nitrogen atmosphere, and rotary evaporate at 55 ° C for 25 minutes to obtain a modified monomer;
[0084] (3) Potassium persulfate and deionized water are mixed at a mass ratio of 1:100 to obtain an initiator solution; acrylate, butyl acrylate, modified monomer and emulsifier mixed solution are mixed at a mass ratio of 1:10:8.5:53.5, pre-emulsified at 40°C and 280r / min for 60min, heated to 80°C, and added with an initiator solution of 11.6 times the mass of acrylic acid at a uniform rate within 30min, continued to stir for 1.5h, heated to 90°C, and added with an initiator solution of 5.8 times the mass of acrylic acid at a uniform rate within 30min, continued to stir for 1.5h, cooled naturally to room temperature, and filtered with a 150-mesh sieve to obtain a modified emulsion;
[0085] (4) Mix cellulose powder and 15% sodium hydroxide solution in a mass ratio of 1:20, soak for 30 minutes, filter, wash with deionized water 4 times, soak in N,N-dimethylacetamide for 12 hours, and filter to obtain activated cellulose; Mix activated cellulose, methacrylic anhydride, lithium chloride-free and N,N-dimethylacetamide in a mass ratio of 1:2:1:10, stir at 60°C and 250rpm for 6 hours, add deionized water and let stand until the precipitate mass remains unchanged, filter, wash with deionized water 4 times, and freeze-dry to obtain modified cellulose;
[0086] (5) According to the mass fraction, 90 parts of modified latex, 5 parts of modified kaolin, 2 parts of modified cellulose, 0.4 parts of perfluorohexylethylene, 0.02 parts of azobisisobutyronitrile and 10 parts of deionized water were dispersed at 1300 rpm for 60 min, 0.015 parts of multifunctional additive AMP-95, 0.09 parts of dispersant CF-10, 0.075 parts of dodecyl alcohol ester, 0.075 parts of propylene glycol and 0.04 parts of defoamer A10 were added, and stirred at 1000 r / min for 30 min to obtain a waterproof and crack-resistant latex paint.
[0087] Comparative Example 5:
[0088] A method for preparing a waterproof and crack-resistant latex paint, comprising the following preparation steps:
[0089] (1) Calcined kaolin, 3-chloropropyltrimethoxysilane and 90% ethanol solution were mixed in a mass ratio of 1:1:45, stirred at 70°C and 250 rpm for 5 h, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol for 4 times, respectively, and dried at 60°C for 12 h to obtain pre-modified kaolin; pre-modified kaolin, allyl diphenylphosphine, nickel bromide and ethylene glycol were mixed in a mass ratio of 1:1.2:0.015:9, stirred at 160°C and 150 rpm for 5 h in a nitrogen atmosphere, naturally cooled to room temperature and filtered, washed with deionized water for 4 times, and dried at 55°C for 15 h to obtain modified kaolin;
[0090] (2) Dicyandiamide, 2-amino-4,6-dichloro-S-triazine and isopropanol were mixed at a mass ratio of 1:2:15, and a 36% hydrochloric acid solution with a mass fraction of 1.04 times the mass of dicyandiamide was added at a constant rate for 2 hours at 100° C., refluxed for 7 hours, rotary evaporated at 85° C. for 1.5 hours, dissolved in anhydrous methanol and filtered, rotary evaporated at 45° C. for 1.5 hours, recrystallized with a 5% ethanol solution and filtered, and dried at 55° C. for 9 hours to obtain a biguanide intermediate; the biguanide intermediate, resorcinol, anhydrous aluminum chloride and chlorobenzene were mixed at a mass ratio of 1:0.5:0.3: 10, stir at 80 ° C and 150 rpm for 4 hours, add 2% hydrochloric acid solution with a mass fraction of 9.5 times the mass of the biguanide intermediate at a uniform rate within 2 hours, distill at atmospheric pressure, heat to 100 ° C, filter while hot, wash with 2% hydrochloric acid solution and deionized water for 4 times, dry at 60 ° C for 12 hours to obtain functionalized biguanide; 4-vinylbenzaldehyde, functionalized biguanide and anhydrous ethanol are mixed at a mass ratio of 1:0.4:25, stir at 50 ° C and 250 rpm for 6 hours in a nitrogen atmosphere, and rotary evaporate at 55 ° C for 25 minutes to obtain a modified monomer;
[0091] (3) Potassium persulfate and deionized water are mixed at a mass ratio of 1:100 to obtain an initiator solution; acrylate, butyl acrylate, modified monomer, 1,3-butadiene and emulsifier mixed solution are mixed at a mass ratio of 1:10:8.5:5:53.5, pre-emulsified at 40°C and 280r / min for 60min, heated to 80°C, and added with an initiator solution of 11.6 times the mass of acrylic acid at a uniform rate within 30min, continued to stir for 1.5h, heated to 90°C, and added with an initiator solution of 5.8 times the mass of acrylic acid at a uniform rate within 30min, continued to stir for 1.5h, cooled naturally to room temperature, and filtered with a 150-mesh sieve to obtain a modified emulsion;
[0092] (4) Mix cellulose powder and 15% sodium hydroxide solution in a mass ratio of 1:20, soak for 30 minutes, filter, wash with deionized water 4 times, soak in N,N-dimethylacetamide for 12 hours, and filter to obtain activated cellulose; Mix activated cellulose, methacrylic anhydride, lithium chloride-free and N,N-dimethylacetamide in a mass ratio of 1:2:1:10, stir at 60°C and 250rpm for 6 hours, add deionized water and let stand until the precipitate mass remains unchanged, filter, wash with deionized water 4 times, and freeze-dry to obtain modified cellulose;
[0093] (5) According to the mass fraction, 90 parts of modified latex, 5 parts of modified kaolin, 2 parts of modified cellulose, 0.02 parts of azobisisobutyronitrile and 10 parts of deionized water were dispersed at 1300 rpm for 60 min, 0.015 parts of multifunctional additive AMP-95, 0.09 parts of dispersant CF-10, 0.075 parts of dodecyl alcohol ester, 0.075 parts of propylene glycol and 0.04 parts of defoamer A10 were added, and stirred at 1000 r / min for 30 min to obtain a waterproof and crack-resistant latex paint.
[0094] Test Case
[0095] 1. Waterproof
[0096] Test method: The waterproof and anti-cracking latex paint obtained in each embodiment and the comparative example are evenly coated on the surface of the steel plate according to GB / T1733, left to stand at 40°C for 3 hours, dried at 80°C for 24 hours, and then edge-sealed with a mixture of rosin and paraffin with a width of 3 cm to obtain a sample to be tested; 2 / 3 of the sample to be tested is immersed in deionized water for 30 days, the bubbling time is recorded, and the waterproofness is judged.
[0097] 2. Crack resistance
[0098] Test method: Pour the waterproof and crack-resistant latex paint obtained in each embodiment and the comparative example into a non-cut right-angle tear mold required by GB / T529 in accordance with GB / T16777, let it stand at 40°C for 3 hours, and then dry it at 80°C for 24 hours before demolding to obtain the sample to be tested (the inner surface of the groove is required to be smooth and flat, without obvious warping). After the sample to be tested is processed, the paint film thickness at three points in the right-angle tear area of the sample specimen is measured using a paint film thickness tester, and the arithmetic mean is taken as the thickness of the sample. Clamp the sample vertically on the universal testing machine as specified, keep the center line of the sample and the center line of the fixture on the same vertical line, stretch it at a speed of 200mm / min until the sample breaks, and record the tear strength Ts when the specimen breaks. 0 .
[0099] 3. Antibacterial
[0100] Test method: 1 g of the waterproof and crack-resistant latex paint obtained in each example and the comparative example was added to the wells of a 12-well cell culture plate, allowed to stand at 40 ° C for 3 h, dried at 80 ° C for 24 h to form a film, placed on a clean bench, sterilized with ultraviolet light for 30 min, and 100 μl of a 1×10 6 The E. coli suspension of 100 CFU / mL was placed in a constant temperature incubator at 37°C and relative humidity greater than 90% for 24 hours, and then 2 ml of saline was accurately added to each well with a pipette. The 12-well cell culture plate was ultrasonically treated for 1 minute to elute the bacteria from the surface of the sample and evenly dispersed in 2 ml of saline. The sample was diluted 10 6After the plate was coated with nutrient agar medium and incubated in a constant temperature incubator at 37°C for 24 hours, the colonies on the plate were counted, N (number of viable bacteria in the test sample), N 0 (Number of live bacteria in blank sample), calculate the inhibition rate
[0101] =(N 0 -N) / N 0 *100%.
[0102] 4. Anti-aging
[0103] Test method: The waterproof and crack-resistant latex paint obtained in each embodiment and the comparative example are poured into a non-cut right-angle tearing mold required by GB / T529 according to GB / T16777, and left to stand at 40°C for 3 hours, and then demolded at 80°C for 24 hours to obtain a sample to be tested; according to GB / T21866, a 30W, 253.7nm ultraviolet lamp specified by the national standard is used to irradiate the test sample for 100 hours at a distance of 0.8m from the test sample, and the tear strength Ts is measured again. 1 , calculate the aging rate = (Ts 0 -Ts 1 ) / Ts 0 *100%.
[0104] Table 1 below shows the analysis results of the waterproof, crack resistance, antibacterial and anti-aging properties of the waterproof and crack resistance latex paints of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0105] Table 1
[0106] Foaming time Tear strength kN / m Antibacterial rate% Aging rate % Example 1 No foaming 4.36 99.92 2.64 Example 2 No foaming 4.38 99.99 2.59 Example 3 No foaming 4.33 99.94 2.67 Comparative Example 1 No foaming 3.67 78.43 2.73 Comparative Example 2 No foaming 4.29 99.89 42.5 Comparative Example 3 No foaming 4.31 35.76 2.96 Comparative Example 4 No foaming 2.09 99.92 3.12 Comparative Example 5 4 days of blistering 4.12 99.87 2.83
[0107] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 1, it can be found that the waterproof and anti-cracking latex paint prepared by the present invention has good waterproof, anti-cracking, antibacterial and anti-aging properties.
[0108] By comparison, the antibacterial rate and tear strength of Examples 1, 2, and 3 are higher than those of Comparative Example 1, indicating that a quaternary phosphonium salt structure similar to the structure and antibacterial mechanism of quaternary ammonium salt antibacterial agent is formed on the calcined kaolin. The atomic radius of phosphorus is larger than that of nitrogen, and the corresponding electronegativity is low, the positive charge is stronger, and the attraction to the negatively charged bacterial cell membrane is also stronger, thereby improving the antibacterial property of the waterproof and crack-resistant latex paint. At the same time, the carbon-carbon double bonds are retained on the surface of the modified kaolin, and are cross-linked with the carbon-carbon double bonds on the modified cellulose and the modified latex to form a network, thereby improving the crack resistance of the waterproof and crack-resistant latex paint.
[0109] By comparison, the aging rates of Examples 1, 2, and 3 are lower than those of Comparative Example 2, indicating that the biguanide intermediate undergoes a substitution reaction with resorcinol, introducing intramolecular hydrogen bonds on the acrylate main chain, imparting the ability to absorb ultraviolet rays, and further improving the aging resistance of the waterproof and crack-resistant latex paint.
[0110] By comparison, the antibacterial rates of Examples 1, 2, and 3 are higher than those of Comparative Example 3, indicating that the biguanide structure is introduced by reacting dicyandiamide with 2-amino-4,6-dichloro-S-triazine to participate in the polymerization of the acrylate main chain. The guanidine group can be ionized and carry a positive charge, and contact with microbial cells through electrostatic attraction, thereby improving the antibacterial properties of the waterproof and crack-resistant latex paint.
[0111] By comparison, the tear strength of Examples 1, 2, and 3 is higher than that of Comparative Example 4, which shows that the conjugated diene 1,3-butadiene forms new covalent bonds after the double bonds are opened by addition polymerization, retains the carbon-carbon double bonds in the modified latex main chain, and can be cross-linked with modified kaolin and modified cellulose in the subsequent curing process to enrich the cross-linking network and improve the crack resistance of the waterproof and crack-resistant latex paint.
[0112] By comparison, the foaming time of Examples 1, 2, and 3 is longer than that of Comparative Example 5, which illustrates that the waterproof performance of the waterproof and crack-resistant latex paint is improved by utilizing perfluorohexylethylene to participate in the curing and cross-linking and introducing hydrophobic perfluoro long chains at the cross-linking nodes.
[0113] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A waterproof and crack-resistant latex paint, characterized in that: The waterproof and crack-resistant latex paint is obtained by mixing modified emulsion, modified kaolin, modified cellulose, perfluorohexylethylene, azobisisobutyronitrile, deionized water, multifunctional additive AMP-95, dispersant CF-10, dodecyl alcohol ester, propylene glycol, and defoamer A10; The modified cellulose is obtained by reacting cellulose powder and methacrylic anhydride; The modified emulsion is obtained by reacting dicyandiamide with 2-amino-4,6-dichloro-S-triazine, resorcinol, and 4-vinylbenzaldehyde in sequence, and then reacting with acrylate, butyl acrylate, and 1,3-butadiene; The modified kaolin is obtained by sequentially reacting calcined kaolin with 3-chloropropyltrimethoxysilane and allyldiphenylphosphine.
2. A method for preparing a waterproof and crack-resistant latex paint, characterized in that: The method comprises the following preparation steps: (1) Calcined kaolin, 3-chloropropyltrimethoxysilane and ethanol solution with a mass fraction of 85% to 95% are mixed in a mass ratio of 1: (0.9 to 1.1): (40 to 50), stirred at 65 to 75°C and 200 to 300 rpm for 4 to 6 hours, naturally cooled to room temperature and filtered, washed with deionized water and anhydrous ethanol for 3 to 5 times respectively, and dried at 55 to 65°C for 11 to 13 hours to obtain a pre-modified kaolin. Kaolin; pre-modified kaolin, allyl diphenylphosphine, nickel bromide and ethylene glycol are mixed in a mass ratio of 1: (1.1-1.3): (0.01-0.02): (8-10), stirred in a nitrogen atmosphere at 155-165° C. and 100-200 rpm for 4-6 hours, naturally cooled to room temperature and then filtered, washed with deionized water for 3-5 times, and dried at 50-60° C. for 14-16 hours to obtain modified kaolin; (2) dicyandiamide, 2-amino-4,6-dichloro-S-triazine and isopropanol were mixed in a mass ratio 1:(1.9-2.1):(14-16) and mix well, add 35%-37% hydrochloric acid solution of 1.03-1.05 times the mass of dicyandiamide at a uniform rate for 1-3h at 95-105°C, reflux for 6-8h, rotary evaporate at 80-90°C for 1-2h, dissolve in anhydrous methanol and filter, rotary evaporate at 40-50°C for 1-2h, recrystallize with 4%-6% ethanol solution and filter, dry at 50-60°C for 8-10h to obtain a biguanide intermediate; mix the biguanide intermediate, resorcinol, anhydrous aluminum chloride and chlorobenzene at a mass ratio of 1:(0.4-0.6):(0.2-0.4):(9-11), and stir at 75-85°C. The method comprises the following steps: stirring at 100 to 200 rpm for 3 to 5 hours, uniformly adding a 1% to 3% hydrochloric acid solution of 9 to 10 times the mass of the biguanide intermediate within 1 to 3 hours, distilling at normal pressure, heating to 95 to 105° C., filtering while hot, washing with a 1% to 3% hydrochloric acid solution and deionized water for 3 to 5 times, and drying at 55 to 65° C. for 11 to 13 hours to obtain a functionalized biguanide; mixing 4-vinylbenzaldehyde, functionalized biguanide and anhydrous ethanol in a mass ratio of 1: (0.3 to 0.5): (20 to 30), stirring at 45 to 55° C. and 200 to 300 rpm in a nitrogen atmosphere for 5 to 7 hours, and rotary evaporating at 50 to 60° C. for 20 to 30 minutes to obtain a modified monomer; (3) Mix potassium persulfate and deionized water at a mass ratio of 1:100 to obtain an initiator solution; mix acrylate, butyl acrylate, modified monomer, 1,3-butadiene and emulsifier mixed solution at a mass ratio of 1:(9-11):(8.4-8.6):(4-6):(53-54), pre-emulsify at 35-45°C and 275-285r / min for 55-65min, heat to 75-85°C, add an initiator solution of 11.5-11.7 times the mass of acrylic acid at a uniform rate within 25-35min, continue stirring for 1-2h, heat to 85-95°C, add an initiator solution of 5.7-5.9 times the mass of acrylic acid at a uniform rate within 25-35min, continue stirring for 1-2h, cool naturally to room temperature, and filter with a 100-200 mesh sieve to obtain a modified emulsion; (4) Mixing cellulose powder and sodium hydroxide solution with a mass fraction of 10% to 20% at a mass ratio of 1:(15-25), soaking for 25-35 minutes, filtering, washing with deionized water for 3-5 times, and then soaking in N,N-dimethylacetamide for 11-13 hours, filtering to obtain activated cellulose; mixing activated cellulose, methacrylic anhydride, lithium chloride-free and N,N-dimethylacetamide at a mass ratio of 1:(1.5-2.5):(0.9-1.1):(9-11), stirring at 55-65° C. and 200-300 rpm for 5-7 hours, adding deionized water and standing until the precipitate mass remains unchanged, filtering, washing with deionized water for 3-5 times, and freeze-drying to obtain modified cellulose; (5) According to the mass fraction, 89-91 parts of modified latex, 4-6 parts of modified kaolin, 1-3 parts of modified cellulose, 0.3-0.5 parts of perfluorohexylethylene, 0.01-0.03 parts of azobisisobutyronitrile and 5-15 parts of deionized water are dispersed at 1200-1400 rpm for 55-65 min, 0.01-0.02 parts of multifunctional auxiliary agent AMP-95, 0.08-0.10 parts of dispersant CF-10, 0.07-0.08 parts of dodecyl alcohol ester, 0.07-0.08 parts of propylene glycol and 0.03-0.05 parts of defoamer A10 are added, and the mixture is stirred at 900-1100 r / min for 25-35 min to obtain a waterproof and crack-resistant latex paint.
3. The method for preparing a waterproof and crack-resistant latex paint according to claim 2, characterized in that: The reaction equation of the pre-modified kaolin in step (1) is:
4. The method for preparing a waterproof and crack-resistant latex paint according to claim 2, characterized in that: The reaction equation of the modified kaolin in step (1) is:
5. The method for preparing a waterproof and crack-resistant latex paint according to claim 2, characterized in that: The reaction equation of the biguanide intermediate in step (2) is:
6. The method for preparing a waterproof and crack-resistant latex paint according to claim 2, characterized in that: The reaction equation of the functionalized biguanide in step (2) is:
7. The method for preparing a waterproof and crack-resistant latex paint according to claim 2, characterized in that: The reaction equation of the modified monomer in step (2) is:
8. The method for preparing a waterproof and crack-resistant latex paint according to claim 2, characterized in that: The emulsifier mixed solution in step (3) is obtained by mixing sodium dodecylbenzene sulfonate, Tween-80 and deionized water in a mass ratio of 1:2.12:
100.
9. The method for preparing a waterproof and crack-resistant latex paint according to claim 2, characterized in that: The reaction equation of the modified emulsion in step (3) is:
10. The method for preparing a waterproof and crack-resistant latex paint according to claim 2, characterized in that: The reaction equation of the modified cellulose in step (4) is: Where R is H or